Farmer Household Income and Farmer’s Wife Contribution in Pattinoang Village Galesong District Takalar Regency - Mirnani, Mirnani; Jumiati, Jumiati; Akbar, Akbar (JURNAL MANAJEMEN AGRIBISNIS; Vol 11 No 01 (2023): Jurnal Managemen AgribisnisDO - 10.24843/JMA.2023.v11.i01.p13, 2023)
This study aims to determine household income and the contribution of the farmer's wife to household income in Pattinoang Village, Galesong District, Takalar Regency. This research was conducted in February-April 2022. The types of data used were qualitative data and quantitative data. The sampling technique in this study used simple random sampling as many as 38 samples from 190 populations. The results showed that the average household income was Rp. 1,946,052 per month and the contribution of the farmer's wife to household income was 38% with an average income of Rp. 742,105 per month.